Armies and Ecosystems in Premodern Europe : The Meuse Region, 1250-1850 - Govaerts, Sander (Arc Humanities Press, 2021)
Military history; Ecological history; war and the environment; Natural barriers in history; wildlife protection, mosasaur; premodern environmentalism
English
Keywords: Military history; Early modern history: c 1450/1500 to c 1700; Early history: c 500 to c 1450/1500; History of science; Environmental archaeology; The environment; Ecological science, the Biosphere; Historical geography; Military history; Ecological history; war and the environment; Natural barriers in history; wildlife protection, mosasaur; premodern environmentalism